Rumen-protected guanidinoacetic acid improves growth performance in beef cattle under chronic heat stress by reshaping gut microbiota and modulating serum metabolism - Geng, Qiang; Lin, Wei; Yang, Libin; Hu, Xiaofei; Qiu, Xinjun (Frontiers in Microbiology, 2025)
This study aimed to investigate the effects of rumen-protected guanidinoacetic acid (RP-GAA) on growth performance, gut microbiota, and serum metabolism in beef cattle under chronic heat stress. A randomized block design was employed to allocate 14 F1 Simmental crossbred cattle (Simmental ♂ × Bos indicus ♀) with an average body weight of 312.5 ± 55.0 kg into two groups (n = 7): a control group was fed a basal diet without RP-GAA and a treatment group was fed the same basal diet supplemented with 10.0 g/day of RP-GAA. During feeding experiments, at 2 p.m., the average temperature increased to 31.5°C, with a relative humidity of 69.5% and a THI of 83.2. All animals are under chronic heat stress. The results indicated that RP-GAA supplementation significantly increased dry matter intake and feed conversion ratio in beef cattle under chronic heat stress (p < 0.05). RP-GAA supplementation tended to reduce respiratory rate or rectal temperature (p < 0.1). Compared to the control group, the treatment group exhibited significantly higher glucose, blood urea nitrogen, total cholesterol, high-density lipoprotein cholesterol, and low-density lipoprotein cholesterol levels (p < 0.05). 16S rRNA gene sequencing revealed that RP-GAA supplementation significantly altered the ruminal microbiota composition, increasing the abundance of Firmicutes and Bacteroidota (p < 0.05), while reducing Proteobacteria (p < 0.01). Principal coordinate analysis (PCoA) and Adonis test (R2 = 0.190, p = 0.003) jointly revealed a distinct difference in fecal microbiota structures between the two groups. Metabolomic analysis identified significant changes in pathways related to creatine synthesis, energy metabolism, and nitrogen utilization, supported by the orthogonal partial least squares discriminant analysis model (R2Y = 0.983, Q2 = 0.836, p < 0.05). These findings suggest that RP-GAAenhances energy homeostasis, supports gut health, and mitigates the adverse effects of heat stress, providing a promising strategy to improve production efficiency and animal welfare in heat-stressed cattle.